Effect of statins treatment on glycemic status and development of new onset diabetes mellitus in a tertiary care teaching hospital: a cross sectional study - Chalapathi Rao, K. N. S. V.; Vankayala, Ashok; Sayana, Suresh Babu; Raju, D. S. S. K. (International Journal of Advances in Medicine, 2019)
Background: Several observational studies, well controlled randomized trials and meta-analyses reported that patients treated with statins has high risk of new onset diabetes mellitus (NODM), but the exact incidence and mechanism is still unclear and controversy. The present study was planned to find out the incidence of prediabetes and NODM and possible mechanism of action. Methods: This was a prospective, cross‑sectional study carried out at the Department of General Medicine for a period of one and half year between August 2017 and February 2019. Normoglycemic patients whose fasting blood glucose levels below 100 mg/dL and at least one year of treatment with statins were recruited in the study. Glycaemic status, development of prediabetes and NODM and insulin resistance were the primary outcomes whereas lipid profile, adverse drug effects of statins were secondary outcomes. Collected data was analysed by suitable statistical methods. Results: A total of 146 patients were recruited and 120 completed the entire study. Mean fasting blood glucose levels before initiation of statin therapy was 89.45±10.21. After one year of statin therapy, patients were separated as prediabetics and new onset diabetics and there mean fasting blood glucose levels were 116.24±12.86 (n=10) and 152.44±20.12 (n=12) respectively. A total of 12 (10.0%) patients were developed NODM and 10 (8.2%) patients developed prediabetes at the end of statin therapy. Atorvastatin 40mg was most frequency prescribed statin followed by Atorvastatin 20mg. A total of 70 (58.3%) study participants developed mild to moderate drug related adverse effects (ADRs), statin‑induced myalgia (55.7%) was the most common ADR. Conclusions: Patients treatment with statins had developed prediabetes and NODM. Atorvastatin 40mg and greater dose significantly induced NODM. Fasting blood glucose levels should be measured periodically with prescription contains higher doses of statins.